Using concept mapping as a tool for conducting research: An analysis of three approaches - Conceição-Runlee, Simone (Cogent social sciences, 2017)
Researchers in a variety of disciplines pursue creative ways to explore complex areas of inquiry. This literature review examines the use of concept maps as a unique tool for conducting research. This study embraces an inclusive definition of concept mapping. Three main approaches for conducting research using concept maps as a tool emerged: relational, cluster, and word frequency. These approaches are included in the different phases of research process such as data collection, analysis, and presentation. Each approach revealed strengths and limitations that researchers need to take into account. This discussion broadens the lens of the meaning of concept mapping as a tool for innovative research approaches.